The thioredoxin system in the psychrophilic eubacterium Pseudoalteromonas haloplanktis - COTUGNO R; SALOMONE G; GRIMALDI P; CECERE F; FALASCA P; RAIMO G; MASULLO M; RUOCCO, MARIA ROSARIA; DE VENDITTIS, EMMANUELE (CSSI (Cell Stress Society International), 2007)
The thioredoxin system, involved in the preservation of the reduced state of cytoplasmic proteins, includes two ubiquitous key components of the intracellular redox balance: thioredoxin (Trx) and thioredoxin reductase (TrxR). Either Trx or TrxR contain a conserved CXXC sequence, switching between disulfide and free dithiol. Trx is a small monomeric protein; TrxR is a NADPH-dependent homodimeric flavoenzyme. The redox cycle in the Trx/TrxR system also involves oscillation between oxidized and reduced form of FAD, using NADPH as electron donor. This report describes the biochemical characterization of the Trx/TrxR system in Pseudoalteromonas haloplanktis (Ph), a psychrophilic eubacterium isolated from marine Antarctic sediments. PhTrxR and PhTrx were obtained as recombinant His-tagged proteins, or isolated from P. haloplanktis cells. The activity of recombinant PhTrxR was evaluated by both DTNB- and thioredoxin-reduction methods and compared with that of endogenous PhTrxR. After exogenous FAD caption, recombinant PhTrxR shows the same activity of the endogenous enzyme. The thermal denaturation of the recombinant enzyme was followed by fluorescence melting curves in the temperature range 5-75°C. Heat inactivation experiments gave a half-life of 10 min at 60°C. However, when studying the thermophilicity with the DTNB-reduction method, maximum activity was reached at 30°C. Like the endogenous counterpart, recombinant PhTrx reduces the insulin disulfides in the presence of either DTT or PhTrxR/NADPH.